Restoring brain barriers: an innovative approach for treating neurological disorders - Campbell, Matthew (My University, 2025)
The complex etiology of neurological disorders is a major challenge to the identification of therapeutic candidates. Tackling brain vascular dysfunction is gaining attention from the scientific community, neurologists and pharmaceutical companies, as a novel disease-modifying strategy. Here, we provide evidence that at least 41% of neurological diseases and related conditions/injuries display a co-pathology of blood-brain and blood-spinal cord barrier alterations and dysfunctions, and we discuss why this figure may represent only a fraction of a larger phenomenon. We further provide clinical evidence that barrier status may contribute to pathological and functional outcomes in patients. Finally, we discuss drug candidates under development to repair brain barriers.
PUBLISHED
Cited by: 0
Keywords: BBB disruption; BSCB disruption; Tight junction; Claudin-5; Alzheimer’s disease; Amyotrophic lateral sclerosis; Huntington’s disease; Multiple sclerosis; Parkinson’s disease; Therapeutic strategies